MODELING OF NONLINEAR DEFORMATION AND BUCKLING OF ELASTIC INHOMOGENEITIES SHELLS - V A Bazhenov; N A Solovei; O P Krivenko; O A Mishchenko (Structural Mechanics of Engineering Constructions and Buildings, 2014)
He paper outlines the fundamentals of the method of solving static problems of geomet- rically nonlinear deformation, buckling, and postbuckling behavior of thin thermoelastic in- homogeneous shells with complex-shaped mid-surface, geometrical features throughout the thickness, and multilayer structure under complex thermomechanical loading. The method is based on the geometrically nonlinear equations of three-dimensional thermoelasticity and the moment finite-element scheme. The method is justified numerically. Comparing solutions with those obtained by other authors and by software LIRA and SCAD is conducted.